Vanadium-doped graphene nanosheet and preparation method thereof
Vanadium-doped graphene nanosheets are prepared by doping vanadium in graphene through electrochemical peeling method, which solves the problem of insufficient electrochemical performance of graphene in the existing technology, and achieves efficient and economical improvement in energy storage application performance.
Patent Information
- Application Number
- CN202311210895.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art is difficult to prepare functionalized graphene nanosheets through simple, safe, controllable, low-cost and high-efficiency methods, especially in energy storage applications.
Vanadium-doped graphene nanosheets were prepared by using the vanadate-containing solution as the electrolyte, and the electrochemical peeling method was used to peel off the graphite raw materials using the electrochemical anode. The method includes doping vanadium into graphene, adjusting the band gap and conductivity of graphene, and improving its electrochemical properties in energy storage applications.
The preparation of vanadium-doped graphene nanosheets is achieved with simple operation, safe and controllable, low cost and high efficiency, significantly improving its electrochemical performance in energy storage applications and enhancing the application potential of materials.
Smart Images

Figure CN119660725A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of graphene, and in particular relates to a vanadium-doped graphene nanosheet and a preparation method thereof. Background Art
[0002] Graphene is a sp 2 A material in which hybrid connected carbon atoms are tightly stacked into a single-layer two-dimensional honeycomb lattice structure. Graphene has excellent optical, electrical, and mechanical properties, and has important application prospects in materials science, micro-nano processing, energy, biomedicine, and drug delivery, and is considered to be a revolutionary material of the future.
[0003] Studies have shown that doping graphene materials with heteroatoms (such as N, B, S, etc.) can significantly change their electronic structure, effectively adjust the graphene band gap, change the conductivity of graphene, and increase the electrochemical performance of graphene in energy storage applications.
[0004] Therefore, it is of great significance to find a method for preparing heteroatom-doped functionalized graphene nanosheets that is simple to operate, safe, controllable, low-cost and efficient. Summary of the invention
[0005] In view of this, the present invention provides a vanadium-doped graphene nanosheet and a preparation method thereof, the main purpose of which is to provide a new type of vanadium-doped graphene nanosheet material.
[0006] On the one hand, the present invention provides a method for preparing vanadium-doped graphene nanosheets, comprising: using a vanadate solution as an electrolyte, and electrochemically stripping a graphite-containing raw material to obtain vanadium-doped graphene nanosheets.
[0007] The present invention can effectively adjust the graphene band gap, change the graphene conductivity, and increase the electrochemical performance of the graphene in energy storage applications by doping vanadium into the graphene.
[0008] Optionally, the vanadate is selected from at least one of potassium vanadate, sodium vanadate and ammonium vanadate.
[0009] The vanadate of the present invention can also be selected from the prior art according to actual needs.
[0010] Optionally, the concentration of the vanadate solution is 0.01 to 10 mol / L.
[0011] Optionally, the concentration of the vanadate solution is 0.01 mol / L to 7 mol / L.
[0012] Optionally, the concentration of the vanadate solution is 1 mol / L to 6 mol / L.
[0013] Optionally, the concentration of the vanadate is independently selected from any value among 0.01mol / L, 0.05mol / L, 0.1mol / L, 0.15mol / L, 0.2mol / L, 0.3mol / L, 0.5mol / L, 1mol / L, 1.6mol / L, 2mol / L, 3mol / L, 4mol / L, 5mol / L, 6mol / L, 7mol / L, 8mol / L, 9mol / L, 10mol / L or a range value between any two of the above points.
[0014] Optionally, the vanadate solution comprises water, vanadate and an organic solvent.
[0015] Optionally, the organic solvent is selected from at least one of ethylene glycol, glycerol and nitriles.
[0016] The organic solvent is added in the method of the present invention to inhibit the oxygen evolution reaction.
[0017] Optionally, the graphite-containing raw material is cleaned with deionized water before being used as an electrochemical anode.
[0018] Optionally, the graphite-containing raw material is selected from at least one of microcrystalline graphite, graphite rods, natural flake graphite, graphite paper and graphite foil.
[0019] Optionally, the voltage applied during the electrochemical stripping is 2 to 20V.
[0020] Optionally, the voltage is independently selected from any value among 2V, 5V, 8V, 10V, 12V, 15V, 18V, 20V or a range of values between any two of the above points.
[0021] Optionally, the electrochemical stripping time is 5 minutes to 48 hours.
[0022] Optionally, the electrochemical anodic stripping time is 0.5 h to 5 h.
[0023] Optionally, the time of the electrochemical anodic stripping is independently selected from any value among 5 min, 20 min, 30 min, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 8 h, 10 h, 12 h, 18 h, 24 h, 30 h, 36 h, 42 h, 48 h, or a range value between any two of the above points.
[0024] Optionally, the temperature of the electrochemical anode stripping is 5-50°C.
[0025] Optionally, the temperature of the electrochemical anodic stripping is independently selected from any value of 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, or a range between any two of the above points.
[0026] The voltage, stripping time, temperature, etc. in the electrochemical stripping method of the present invention can be adjusted according to actual needs.
[0027] Optionally, in the electrochemical stripping, the electrochemical anode is a graphite-containing raw material, and the electrochemical cathode is a conductive electrochemically inert material; the conductive electrochemically inert material is selected from at least one of glassy carbon, platinum, graphite and nickel.
[0028] Optionally, the ratio of the area of the electrochemical anode immersed in the electrolyte to the area of the electrochemical cathode immersed in the electrolyte is 0.2-12.
[0029] Optionally, the ratio of the area of the electrochemical anode immersed in the electrolyte to the area of the electrochemical cathode immersed in the electrolyte is independently selected from any value among 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12 or the range between any two of the above points.
[0030] In the method of the present invention, the appropriate stripping speed and the speed of the oxygen evolution reaction are regulated by controlling the area ratio of the anode and the cathode.
[0031] Optionally, the horizontal distance between the electrochemical cathode and the electrochemical anode immersed in the electrolyte is 1 to 3 cm.
[0032] Optionally, the distance between the electrochemical cathode and the electrochemical anode is independently selected from any value among 1 cm, 1.1 cm, 1.2 cm, 1.3 cm, 1.4 cm, 1.5 cm, 1.6 cm, 1.7 cm, 1.8 cm, 1.9 cm, 2 cm, 2.1 cm, 2.2 cm, 2.3 cm, 2.4 cm, 2.5 cm, 2.6 cm, 2.7 cm, 2.8 cm, 2.9 cm, 3 cm, or a range between any two of the above points.
[0033] When the horizontal distance between the anode and the cathode in the method of the present invention is controlled within 3 cm, the quality of the peeled graphene, such as the number of layers and the size, is relatively good.
[0034] Optionally, the method further comprises: after electrochemical anode exfoliation of graphite, the exfoliation product is washed and ultrasonically dispersed to obtain vanadium-doped graphene nanosheet slurry, and the slurry is dried to obtain vanadium-doped graphene nanosheets.
[0035] Optionally, the washing method is selected from at least one of dialysis, centrifugation and filtration.
[0036] Optionally, the drying method is selected from at least one of natural air drying, normal pressure heating drying, vacuum drying, spray drying and freeze drying;
[0037] Optionally, the ultrasonic dispersion time is 1 h to 2 h.
[0038] Optionally, the ultrasonic dispersion time is independently selected from any value among 1 h, 1.2 h, 1.4 h, 1.5 h, 1.6 h, 1.8 h, 2 h, or a range between any two of the above points.
[0039] The present invention provides a specific method for preparing vanadium-doped graphene nanosheets by electrochemical anode exfoliation of graphite, comprising the following steps:
[0040] An aqueous solution containing vanadate is used as an electrolyte, a raw material containing graphite is used as an electrochemical anode, and a conductive electrochemically inert material is used as an electrochemical cathode;
[0041] The electrolyte, electrochemical anode and electrochemical cathode constitute an electrochemical circuit;
[0042] A voltage is applied between the electrochemical cathode and the electrochemical anode, and the electrochemical anode exfoliates graphite to prepare vanadium-doped graphene nanosheets.
[0043] The method for preparing vanadium-doped graphene nanosheets by electrochemical anode stripping of graphite is achieved by the following steps: firstly, a soluble vanadate is used as a stripping electrolyte, a conductive material is used as a counter electrode connected to the negative electrode of a direct current power supply, graphite is used as a raw material and connected to the positive electrode of the direct current power supply, and under normal temperature and pressure conditions, a suitable cell voltage is selected to perform electrochemical stripping, and the stripping product is washed and ultrasonically dispersed to obtain vanadium-doped graphene nanosheet slurry, and then dried to obtain vanadium-doped graphene nanosheet powder.
[0044] In the present invention, "room temperature" refers to 10 to 45°C.
[0045] In a second aspect, the present invention provides a vanadium-doped graphene nanosheet, wherein the vanadium-doped graphene nanosheet is prepared by the above-mentioned method for preparing the vanadium-doped graphene nanosheet.
[0046] Optionally, the size of the vanadium-doped graphene nanosheets is 0.5 to 200 μm.
[0047] Optionally, the number of layers of the vanadium-doped graphene nanosheets is 1 to 7.
[0048] Optionally, the surface oxygen content of the vanadium-doped graphene nanosheets is 15-25 at%.
[0049] Optionally, the content of vanadium element on the surface of the vanadium-doped graphene nanosheets is 5 to 10 at %.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] 1) The method for preparing vanadium-doped graphene nanosheets by electrochemical anodic exfoliation of graphite provided by the present invention successfully prepared vanadium-doped graphene nanosheets.
[0052] 2) The method for preparing vanadium-doped graphene nanosheets by electrochemical anodic exfoliation of graphite provided by the present invention is simple to operate, safe and controllable, low-cost and high-efficiency.
[0053] 3) The present invention is relatively more environmentally friendly and has less corrosion to the electrochemical stripping device. It uses a soluble vanadate as an electrolyte and a method of electrochemical anode stripping of graphite to synthesize vanadium-doped graphene nanosheets in one step. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 is a slurry image of vanadium-doped graphene nanosheets prepared in Example 1 of the present invention;
[0055] Figure 2 is a scanning electron microscope image of the vanadium-doped graphene nanosheet prepared in Example 1 of the present invention;
[0056] Figure 3 is a transmission electron microscope image of the vanadium-doped graphene nanosheet prepared in Example 1 of the present invention;
[0057] Figure 4 is an atomic force microscopic analysis image of the few-layer vanadium-doped graphene nanosheet prepared in Example 1 of the present invention;
[0058] Figure 5 is an atomic force microscopic height distribution diagram of the few-layer vanadium-doped graphene nanosheet prepared in Example 1 of the present invention;
[0059] Figure 6 This is the X-ray photoelectron spectrum of vanadium-doped graphene nanosheets prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0060] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.
[0061] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.
[0062] The analysis method in the examples of this application is as follows:
[0063] SEM analysis was performed using a Quanta-200F scanning electron microscope.
[0064] TEM analysis was performed using a HT-7700 transmission electron microscope.
[0065] AFM analysis was performed using NanoWizard atomic force microscopy.
[0066] XPS analysis was performed using a Thermofisher Escalab 250Xi+ quasi-in-situ X-ray photoelectron spectrometer.
[0067] Example 1
[0068] Take 100 mL of 0.8 mol / L sodium vanadate solution and put it into a 250 mL beaker. Use expanded graphite paper as the graphite anode. 2 The platinum sheet was used as the cathode and connected to a DC power supply. The bottom end face of the graphite anode was vertically immersed in the upper liquid surface of sodium vanadate, and the platinum cathode was completely immersed in the position below the interface of the sodium vanadate solution. The area ratio of the graphite electrode and the platinum sheet electrode immersed in the electrolyte solution was 1. The two electrodes were placed in parallel with a spacing of 1 cm. The DC power supply was turned on and the constant voltage was controlled to 10V. The stripping was performed at room temperature for 1h. A small amount of bubbles was generated on the bottom end face of the cathode and a very small amount of bubbles were generated in the anode area. The bubbles were discharged vertically upward from the system. Under the influence of interfacial tension, intercalation, and electrochemical force, the surface tension of the graphite anode was significantly increased. The ... Under the combined effect, a large amount of graphene is continuously peeled off from the bottom end face of the anode. As the electrolysis process proceeds, the bottom end face of the graphite anode is continuously consumed and floats on the surface of the electrolyte solution. The final mixed system of graphene and potassium vanadate solution is filtered and fully washed with deionized water, and then 100 ml of ethanol is added for dispersion. Ultrasonic dispersion with a power of 100 W is used for 1 hour to obtain graphene slurry, which is recorded as sample 1. The above graphene slurry is naturally dried at room temperature and pressure to obtain graphene powder. The above-obtained graphene slurry is further diluted to light black and dripped onto a flat mica sheet. After drying with an infrared lamp, atomic force microscopy observation is performed. The above-mentioned graphene slurry with the same concentration is dripped onto copper coral for scanning electron microscopy and transmission electron microscopy tests.
[0069] Example 2
[0070] Take 100 mL of 0.5 mol / L sodium vanadate solution and put it into a 250 mL beaker. Use expanded graphite paper as the graphite anode. 2The platinum sheet was used as the cathode and connected to a DC power supply. The bottom end face of the graphite anode was vertically immersed in the upper liquid surface of sodium vanadate, and the platinum cathode was completely immersed in the position below the interface of the sodium vanadate solution. The area ratio of the graphite electrode and the platinum sheet electrode immersed in the electrolyte solution was 1. The two electrodes were placed in parallel with a spacing of 1 cm. The DC power supply was turned on and the constant voltage was controlled to 10V. The stripping was performed at room temperature for 1h. A small amount of bubbles was generated on the bottom end face of the cathode and a very small amount of bubbles were generated in the anode area. The bubbles were discharged vertically upward from the system. Under the influence of interfacial tension, intercalation, and electrochemical force, the surface tension of the graphite anode was significantly increased. The ... Under the combined effect, a large amount of graphene is continuously peeled off from the bottom end face of the anode. As the electrolysis process proceeds, the bottom end face of the graphite anode is continuously consumed and floats on the surface of the electrolyte solution. The final mixed system of graphene and potassium vanadate solution is filtered and fully washed with deionized water, and then 100 ml of ethanol is added for dispersion. Ultrasonic dispersion with a power of 100 W is used for 1 hour to obtain graphene slurry, which is recorded as sample 2. The above graphene slurry is naturally dried at room temperature and pressure to obtain graphene powder. The above-obtained graphene slurry is further diluted to light black and dripped onto a flat mica sheet. After drying with an infrared lamp, atomic force microscopy observation is performed. The above-mentioned graphene slurry with the same concentration is dripped onto copper coral for scanning electron microscopy and transmission electron microscopy tests.
[0071] Example 3
[0072] Take 100 mL of 1 mol / L sodium vanadate solution and put it into a 250 mL beaker. Use expanded graphite paper as the graphite anode. 2 The platinum sheet was used as the cathode and connected to a DC power supply. The bottom end face of the graphite anode was vertically immersed in the upper liquid surface of sodium vanadate, and the platinum cathode was completely immersed in the position below the interface of the sodium vanadate solution. The area ratio of the graphite electrode and the platinum sheet electrode immersed in the electrolyte solution was 1. The two electrodes were placed in parallel with a spacing of 1 cm. The DC power supply was turned on and the constant voltage was controlled to 10V. The stripping was performed at room temperature for 1h. A small amount of bubbles was generated on the bottom end face of the cathode and a very small amount of bubbles were generated in the anode area. The bubbles were discharged vertically upward from the system. Under the influence of interfacial tension, intercalation, and electrochemical force, the surface tension of the graphite anode was significantly increased. The ... Under the combined effect, a large amount of graphene is continuously peeled off from the bottom end face of the anode. As the electrolysis process proceeds, the bottom end face of the graphite anode is continuously consumed and floats on the surface of the electrolyte solution. The final mixed system of graphene and potassium vanadate solution is filtered and fully washed with deionized water, and then 100 ml of ethanol is added for dispersion. Ultrasonic dispersion with a power of 100 W is used for 1 hour to obtain graphene slurry, which is recorded as sample 1. The above graphene slurry is naturally dried at room temperature and pressure to obtain graphene powder. The above-obtained graphene slurry is further diluted to light black and dripped onto a flat mica sheet. After drying with an infrared lamp, atomic force microscopy observation is performed. The above-mentioned graphene slurry with the same concentration is dripped onto copper coral for scanning electron microscopy and transmission electron microscopy tests.
[0073] Example 4
[0074] Take 100 mL of 2 mol / L potassium vanadate solution and put it into a 250 mL beaker. Use expanded graphite paper as the graphite anode. 2 The platinum sheet was used as the cathode and connected to a DC power supply. The bottom end face of the graphite anode was vertically immersed in the upper liquid surface of sodium vanadate, and the platinum cathode was completely immersed in the position below the interface of the sodium vanadate solution. The area ratio of the graphite electrode and the platinum sheet electrode immersed in the electrolyte solution was 1. The two electrodes were placed in parallel with a spacing of 1 cm. The DC power supply was turned on and the constant voltage was controlled to 10V. The stripping was performed at room temperature for 1h. A small amount of bubbles was generated on the bottom end face of the cathode and a very small amount of bubbles were generated in the anode area. The bubbles were discharged vertically upward from the system. Under the influence of interfacial tension, intercalation, and electrochemical force, the surface tension of the graphite anode was significantly increased. The ... Under the combined effect, a large amount of graphene is continuously peeled off from the bottom end face of the anode. As the electrolysis process proceeds, the bottom end face of the graphite anode is continuously consumed and floats on the surface of the electrolyte solution. The final mixed system of graphene and potassium vanadate solution is filtered and fully washed with deionized water, and then 100 ml of ethanol is added for dispersion. Ultrasonic dispersion with a power of 100 W is used for 1 hour to obtain graphene slurry, which is recorded as sample 1. The above graphene slurry is naturally dried at room temperature and pressure to obtain graphene powder. The above-obtained graphene slurry is further diluted to light black and dripped onto a flat mica sheet. After drying with an infrared lamp, atomic force microscopy observation is performed. The above-mentioned graphene slurry with the same concentration is dripped onto copper coral for scanning electron microscopy and transmission electron microscopy tests.
[0075] Example 5
[0076] Take 100 mL of 2.4 mol / L potassium vanadate solution and put it into a 250 ml beaker. Use expanded graphite paper as the graphite anode. 2The platinum sheet was used as the cathode and connected to a DC power supply. The bottom end face of the graphite anode was vertically immersed in the upper liquid surface of sodium vanadate, and the platinum cathode was completely immersed in the position below the interface of the sodium vanadate solution. The area ratio of the graphite electrode and the platinum sheet electrode immersed in the electrolyte solution was 1. The two electrodes were placed in parallel with a spacing of 1 cm. The DC power supply was turned on and the constant voltage was controlled to 10V. The stripping was performed at room temperature for 1h. A small amount of bubbles was generated on the bottom end face of the cathode and a very small amount of bubbles were generated in the anode area. The bubbles were discharged vertically upward from the system. Under the influence of interfacial tension, intercalation, and electrochemical force, the surface tension of the graphite anode was significantly increased. The ... Under the combined effect, a large amount of graphene is continuously peeled off from the bottom end face of the anode. As the electrolysis process proceeds, the bottom end face of the graphite anode is continuously consumed and floats on the surface of the electrolyte solution. The final mixed system of graphene and potassium vanadate solution is filtered and fully washed with deionized water, and then 100 ml of ethanol is added for dispersion. Ultrasonic dispersion with a power of 100 W is used for 1 hour to obtain graphene slurry, which is recorded as sample 1. The above graphene slurry is naturally dried at room temperature and pressure to obtain graphene powder. The above-obtained graphene slurry is further diluted to light black and dripped onto a flat mica sheet. After drying with an infrared lamp, atomic force microscopy observation is performed. The above-mentioned graphene slurry with the same concentration is dripped onto copper coral for scanning electron microscopy and transmission electron microscopy tests.
[0077] Example 6
[0078] Take 100 mL of 3.6 mol / L sodium vanadate solution and put it into a 250 mL beaker. Use expanded graphite paper as the graphite anode. 2 The platinum sheet was used as the cathode and connected to a DC power supply. The bottom end face of the graphite anode was vertically immersed in the upper liquid surface of sodium vanadate, and the platinum cathode was completely immersed in the position below the interface of the sodium vanadate solution. The area ratio of the graphite electrode and the platinum sheet electrode immersed in the electrolyte solution was 1. The two electrodes were placed in parallel with a spacing of 1 cm. The DC power supply was turned on and the constant voltage was controlled to 10V. The stripping was performed at room temperature for 1h. A small amount of bubbles was generated on the bottom end face of the cathode and a very small amount of bubbles were generated in the anode area. The bubbles were discharged vertically upward from the system. Under the influence of interfacial tension, intercalation, and electrochemical force, the surface tension of the graphite anode was significantly increased. The ... Under the combined effect, a large amount of graphene is continuously peeled off from the bottom end face of the anode. As the electrolysis process proceeds, the bottom end face of the graphite anode is continuously consumed and floats on the surface of the electrolyte solution. The final mixed system of graphene and potassium vanadate solution is filtered and fully washed with deionized water, and then 100 ml of ethanol is added for dispersion. Ultrasonic dispersion with a power of 100 W is used for 1 hour to obtain graphene slurry, which is recorded as sample 1. The above graphene slurry is naturally dried at room temperature and pressure to obtain graphene powder. The above-obtained graphene slurry is further diluted to light black and dripped onto a flat mica sheet. After drying with an infrared lamp, atomic force microscopy observation is performed. The above-mentioned graphene slurry with the same concentration is dripped onto copper coral for scanning electron microscopy and transmission electron microscopy tests.
[0079] Test Example 1 Morphology Characterization
[0080] Sample 1 is in the form of a slurry, such as Figure 1 As shown; the slurries of other samples are Figure 1 resemblance.
[0081] SEM image of sample 1, as shown Figure 2 As shown; Figure 2 The SEM images of the other samples are similar to those of Figure 2 resemblance.
[0082] TEM image of sample 1, such as Figure 3 As shown; Figure 3 It shows that the individual vanadium-doped graphene nanosheets are only slightly stacked, and the vanadium-doped graphene nanosheets are peeled off by electrochemical cathode. The TEM images of other samples are similar to Figure 3 resemblance.
[0083] Atomic force microscopy analysis of few-layer graphene of sample 1, as shown in Figure 4 As shown; Figure 4 It shows that the vanadium-doped graphene nanosheets in sample 1 contain single-layer or few-layer vanadium-doped graphene nanosheets.
[0084] Atomic force microscopy height distribution of few-layer graphene of sample 1, as shown in Figure 5 As shown; Figure 5 It shows that the vanadium-doped graphene nanosheets in sample 1 contain single-layer or few-layer vanadium-doped graphene nanosheets.
[0085] Atomic force microscopy height distribution of few-layer graphene of sample 1, as shown in Figure 6 As shown; Figure 6 It shows that there are vanadium elements in different valence states in the vanadium-doped graphene nanosheets in sample 1.
[0086] The electrochemical performance of the vanadium-doped graphene supercapacitor provided by the present invention includes the double electric layer of the graphene nanosheet itself, and the pseudocapacitive electrochemical performance provided by the oxygen-containing functional groups and the multivalent vanadium element. Compared with pure graphene, the capacity of the pseudocapacitive part of the electrochemical performance is significantly improved.
[0087] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing vanadium-doped graphene nanosheets, characterized in that: The preparation method comprises: using a vanadate solution as an electrolyte, and electrochemically stripping a graphite-containing raw material to obtain vanadium-doped graphene nanosheets.
2. The method for preparing vanadium-doped graphene nanosheets according to claim 1, characterized in that: The vanadate is selected from at least one of potassium vanadate, sodium vanadate and ammonium vanadate.
3. The method for preparing vanadium-doped graphene nanosheets according to claim 1, characterized in that: The concentration of the vanadate solution is 0.01-10 mol / L.
4. The method for preparing vanadium-doped graphene nanosheets according to claim 1, characterized in that: The vanadate solution comprises water, vanadate and an organic solvent; the organic solvent is selected from at least one of ethylene glycol, glycerol and nitriles; Preferably, the graphite-containing raw material is selected from at least one of microcrystalline graphite, graphite rods, natural flake graphite, graphite paper and graphite foil.
5. The method for preparing vanadium-doped graphene nanosheets according to claim 1, characterized in that: The voltage applied in the electrochemical stripping is 2 to 20 V; Preferably, the electrochemical stripping time is 5 minutes to 48 hours; the electrochemical anodic stripping temperature is 5 to 50°C.
6. The method for preparing vanadium-doped graphene nanosheets according to claim 1, characterized in that: In the electrochemical stripping, the electrochemical anode is a graphite-containing raw material, and the electrochemical cathode is a conductive electrochemically inert material; the conductive electrochemically inert material is selected from at least one of glassy carbon, platinum, graphite and nickel.
7. The method for preparing vanadium-doped graphene nanosheets according to claim 6, characterized in that: The ratio of the area of the electrochemical anode immersed in the electrolyte to the area of the electrochemical cathode immersed in the electrolyte is 0.2 to 12; Preferably, the horizontal distance between the electrochemical cathode and the electrochemical anode immersed in the electrolyte is 1 to 3 cm.
8. The method for preparing vanadium-doped graphene nanosheets according to claim 1, characterized in that: The method further comprises: after electrochemical anode exfoliation of graphite, the exfoliation product is washed and ultrasonically dispersed to obtain vanadium-doped graphene nanosheet slurry, and the slurry is dried to obtain vanadium-doped graphene nanosheets; Preferably, the washing method is selected from at least one of dialysis, centrifugation and filtration; The drying method is selected from at least one of natural air drying, normal pressure heating drying, vacuum drying, spray drying and freeze drying; The ultrasonic dispersion time is 1 to 2 hours.
9. A vanadium-doped graphene nanosheet, characterized in that: The vanadium-doped graphene nanosheets are prepared by the method for preparing vanadium-doped graphene nanosheets according to any one of claims 1 to 8.
10. The vanadium-doped graphene nanosheet according to claim 9, characterized in that: The size of the vanadium-doped graphene nanosheets is 0.5 to 200 μm; Preferably, the number of layers of the vanadium-doped graphene nanosheets is 1 to 7; Preferably, the surface oxygen content of the vanadium-doped graphene nanosheets is 15 to 25 at %; Preferably, the content of vanadium element on the surface of the vanadium-doped graphene nanosheets is 5 to 10 at %.
Citation Information
Patent Citations
A preparation method and application of electrochemically stripped graphene-based metal oxide
CN109088064A
Electrolyte for electrochemical stripping of two- dimensional nanometer materials
CN109368626A
Vanadium pentoxide nanosheet and graphene composite material preparation method
CN109461914A
Vanadium-doped tungsten disulfide / graphene oxide composite electrode material and preparation method and application thereof
CN111874950A
Graphene / LixV2O5 composite electrode material, preparation method and application thereof
CN114275812A